Characteristics, body mass index (bmi), and upper arm circumference in first trimester pregnant women - Putri Santy; Yulia Fitri (Institute of Computer Science (IOCS), 2023)
Age, education, occupation, and parity affect the nutritional status of pregnant women. Body Mass Index (BMI) and Upper Arm Circumference, these two measurements become routine services for pregnant women who have their pregnancy checked. But the number of pregnant women who are subjected to Upper Arm Circumference examinations does not reach 100%. This study aims to determine the characteristics, the proportion of BMI, and Upper Arm Circumference in pregnant women in the I trimester in the Darul Imarah Health Center Working Area, Aceh Besar Regency. This descriptive study included 142 first-trimester pregnant women recorded in the KIA room register book of the Darul Imarah Health Center, Aceh Besar Regency. The data comes from data based from January to June 2022. The results showed that the age characteristics of most respondents ranged from 20-35 years old, had secondary education, did not work, and had multigravida pregnancies. For BMI and Upper Arm Circumference results, the average body mass index and upper arm circumference size are in the normal category. It is hoped that health workers will improve health services for pregnant women about fulfilling nutrition before and during pregnancy.